If f(x) = 2x-3 and g(x) = x+1 find fog(3) and gof(-2)?

Expert Answers

An illustration of the letter 'A' in a speech bubbles

f(x) = 2x-3

g(x) = x+1

`f_og(3)` means that we get the value of f(x) when x = g(3)

g(x) = x+1

g(3) = 3+1 = 4

`f_og(3) ` = f(4) = 2(4)-3 = 5

`g_of(-2)` means that we get the value of g(x) when x =...

See
This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Get 48 Hours Free Access

f(x) = 2x-3

g(x) = x+1

 

`f_og(3)` means that we get the value of f(x) when x = g(3)


g(x) = x+1

g(3) = 3+1 = 4

 

`f_og(3) ` = f(4) = 2(4)-3 = 5

 

`g_of(-2)` means that we get the value of g(x) when x = f(-2)

f(x) = 2x-3

f(-2) = 2*-2-3 = -7

 

`g_of(-2) ` = g(-7) = -7+1 = -6

 

Therefore;

`f_og(3) = 5`

`g_of(-2) = -6`

 

 

Approved by eNotes Editorial Team